The importance of social euphemisms and their application to british and kazakh press (Eurasian Journal of Philology Science and Education, 2021)
The aim of this article is to explore the social euphemisms that are used in Kazakh language. It focuses on relations of taboo words and euphemism. Euphemism is an important technique that shows us how to deal with social taboos in a society. Taboos have been around for many centuries derived from customs and traditions of distinct cultures. Euphemistic expressions facilitate the avoidance of direct speaking taboo words by offering a category of replacement words. The article shows peculiarities of the usage of social euphemisms in Kazakh culture. It presents unique views on euphemisms to show attitudes of various scholars towards the phenomenon. The article focuses on the description of meanings of euphemisms found in certain situations. The objectives of the analysis are: to identify social euphemisms used in today’s English and Kazakh online newspapers and examine why they are used in certain contexts. The article analyzes some euphemisms used in the British and Kazakh online newspapers. It compares euphemisms in the British press, with euphemism in Kazakh press and their underlying meanings. Social euphemisms from the online English newspapers The Guardian, The Telegraph, Express, Independent and Kazakh online newspapers Kazinform, AqJol and Қазақстан Zaman are subjected to analysis.